2016
DOI: 10.1016/j.ijsolstr.2016.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the tilted flat punch in couple-stress elasticity

Abstract: Abstract. In the present paper we explore the response of a half-plane indented by a tilted flat punch with sharp corners in the context of couple-stress elasticity theory. Contact conditions arise in a number of modern engineering applications ranging from structural and geotechnical engineering to micro and nanotechnology. As the contact scales reduce progressively the effects of the microstructure upon the macroscopic material response cannot be ignored. The generalized continuum theory of couple-stress ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…The results showed that characteristic material length was a significant influencing factor on the contact behaviors of microstructured materials. A similar problem was later investigated by Gourgiotis and Zisis [22] for a wedge punch and a cylindrical punch and by Gourgiotis et al [23] for a tilted flat punch. Applying the Fourier integral transform and the generalized stress function method and considering the influence of heat flux, steady-state thermomechanical contact of a smooth flat punch was investigated by considering the influence of the couple stress [24].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…The results showed that characteristic material length was a significant influencing factor on the contact behaviors of microstructured materials. A similar problem was later investigated by Gourgiotis and Zisis [22] for a wedge punch and a cylindrical punch and by Gourgiotis et al [23] for a tilted flat punch. Applying the Fourier integral transform and the generalized stress function method and considering the influence of heat flux, steady-state thermomechanical contact of a smooth flat punch was investigated by considering the influence of the couple stress [24].…”
Section: Introductionmentioning
confidence: 79%
“…Referring to [8,23], the constitutive equations can be written as…”
Section: Basic Equations Of Couple-stress Elasticity Theorymentioning
confidence: 99%
“…Recently, experimental observations at the micro-and nano-scale have evidenced size-effects [9,12,22,37], which cannot be described with local constitutive models. Therefore, an enhanced modelling has been introduced, which becomes particularly useful when large strain gradient are involved, as in contact mechanics [19,38] indentation processes [8,15], fracture [18,28], and shear band formation [14,32].…”
Section: Introductionmentioning
confidence: 99%
“…For the isotropic case, the constrained Cosserat theory introduces material length scales which can be related to the intrinsic material microstructure [21,22,23,24]. The constrained Cosserat theory has been recently employed successfully to model size effects in microstructured materials in, among other areas, fracture [25,26,27,28,29,30,31], contact [32,33,34], stress localization [35,36,37,38], and wave propagation problems [39,40,41,42].…”
Section: Introductionmentioning
confidence: 99%